2019
DOI: 10.1136/bmjopen-2018-026752
|View full text |Cite
|
Sign up to set email alerts
|

Difluprednate versus Prednisolone Acetate after Cataract Surgery: a Systematic Review and Meta-Analysis

Abstract: ObjectiveTopical steroids are the cornerstone in controlling the inflammation after cataract surgery. Prednisolone acetate and difluprednate are the two main products for this purpose. However, it is unclear which one should be used in terms of effectiveness and safety.DesignSystematic review and meta-analysis.Data sourcesMedline via PubMed, Cochrane Central Register of Controlled Trials, Web of science and clinicaltrials.gov were searched through 10 January 2018, and updated on 20 July 2019, in addition to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…4 The continued popularity of prednisolone is interesting given that it is less potent than difluprednate. Although the 2 steroids have not been directly compared as a means of preventing corneal graft rejection, a 2018 systematic review and meta-analysis 14 of 6 RCTs showed that difluprednate was superior to prednisolone acetate during the first 2 weeks postcataract surgery. These results warrant further investigation of steroid use for keratoplasty outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The continued popularity of prednisolone is interesting given that it is less potent than difluprednate. Although the 2 steroids have not been directly compared as a means of preventing corneal graft rejection, a 2018 systematic review and meta-analysis 14 of 6 RCTs showed that difluprednate was superior to prednisolone acetate during the first 2 weeks postcataract surgery. These results warrant further investigation of steroid use for keratoplasty outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…16 The systematic review and meta-analysis from 2018 also reported no statistically significant difference in high IOP events between both drugs across studies and deemed both agents safe for IOP rise. 14…”
Section: Discussionmentioning
confidence: 99%
“…Newer techniques in phacoemulsification and the advent of safer topical steroids and non-steroidal drugs (NSAIDs) administration have led to quick visual rehabilitation after cataract surgery. Yet, postoperative inflammation in the form of AC reaction and CME continues to be the major factors causing sub-optimal visual outcomes [ 27 ]. Corticosteroids play a vital role in the treatment of this inflammation by inhibiting the release of arachidonic acid from cell membrane phospholipids and prevent the production of leukotrienes and prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroids play a vital role in the treatment of this inflammation by inhibiting the release of arachidonic acid from cell membrane phospholipids and prevent the production of leukotrienes and prostaglandins. Older potent topical corticosteroids like prednisolone acetate and dexamethasone are now being replaced with newer and safer steroids like difluprednate and fluorometholone [ 27 ]. The known advantages of difluprednate related to its better patient compliance over prednisolone are its better bioavailability, enhanced penetration and dose uniformity apart from being preservative-free.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation